Shape-memory polymers for multiple applications in the materials world - Pilate, Florence; Toncheva, Antoniya; Dubois, Philippe; Raquez, Jean-Marie (European polymer journal, 2016)
[Display omitted] •SMPs are an emerging class of smart polymer materials with multi-responsiveness.•Recent trends in the field of SMPs (conception, fabrication, modeling) are outlined.•A new generation multi-functional SMPs containing nanosized fillers is described.•The nanocomposites have enhanced mechanical, thermal and shape-memory properties.•SMPs are of great interest to fundamental research and technological innovation. Shape-memory polymers (SMPs) as stimuli-responsive shape-changing polymers are of great interest for fundamental research and technological innovation. In this contribution, a brief review of the recent trends in the field of SMPs is presented with particular focus on their structure, shape-memory effects and working mechanism. A special attention is paid to smart multi-responsive and multi-functional SMP materials as emerging technological class. They are mainly described as shape-memory nanocomposites (SMCs) where the incorporation of functional (in)organic nanofillers in the SMP matrices is purposely carried out. Potential applications of the SMCs-based materials as medical and biomimetic devices, self-healing systems, self-deployable structures, actuators, sensors, etc. or their direct implementation in the industry are finally outlined.